2019
DOI: 10.1111/jpn.13062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Epigallocatechin‐3‐gallate on small intestinal morphology, antioxidant capacity and anti‐inflammatory effect in heat‐stressed broilers

Abstract: This study was to investigate the effects of Epigallocatechin‐3‐gallate (EGCG) on intestinal morphology, antioxidant capacity and anti‐inflammatory response in heat‐stressed broiler. A total of 192 2‐week‐old Arbour Acres broilers chickens were divided into four groups with six replicates per group and eight chickens per replicate: one thermoneutral control group (28°C, group TN), which was fed the basal diet; and three cyclic high‐temperature groups (35°C from 7:00 to 19:00 hr; 28°C from 19:00 hr to 7:00 hr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
(60 reference statements)
1
26
0
Order By: Relevance
“…The gastrointestinal tract is primarily considered as one of the main target organs affected by heat stress, and a variety of adverse changes can be observed, including injured intestinal morphology and impairment of intestinal barrier integrity (Alhenaky et al., 2017; Lambert, 2009; Song et al., 2019). Villus height and crypt depth, serving as criteria that reflect intestinal morphology, are indicative of gut function and health (Uni, Noy, & Sklan, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gastrointestinal tract is primarily considered as one of the main target organs affected by heat stress, and a variety of adverse changes can be observed, including injured intestinal morphology and impairment of intestinal barrier integrity (Alhenaky et al., 2017; Lambert, 2009; Song et al., 2019). Villus height and crypt depth, serving as criteria that reflect intestinal morphology, are indicative of gut function and health (Uni, Noy, & Sklan, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Served as the digestive and absorbing organ and the largest immune organ in the body, the gastrointestinal tract is particularly responsive to heat stress (Abuajamieh et al., 2018). Accumulating studies have demonstrated that heat stress can damage the intestinal mucosal epithelium of chickens (Burkholder, Thompson, Einstein, Applegate, & Patterson, 2008; Garriga et al., 2006; Quinteiro‐Filho et al., 2010; Song et al., 2013, 2019), which allows endotoxins and pathogens passage from the gastrointestinal lumen into bloodstream, thereby leading to local and systemic inflammation and multiple‐organ dysfunction (Alhenaky, Abdelqader, Abuajamieh, & Al‐Fataftah, 2017; Lambert, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al reported that EGCG partially improved the antioxidant system in vanadium-challenged hens [ 11 ]. Moreover, previous studies of broilers subjected to cyclic chronic HS found that dietary EGCG supplementation can effectively improve growth performance, antioxidant capacity, and the expression of nuclear factor erythroid 2-related 2 ( Nrf2 ) in liver and jejunum, kidney, and ovary [ 12 , 13 , 14 ]. Nevertheless, there exists no report on the effect and mechanism of action of EGCG on meat quality and antioxidant function in broilers under AHS.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [ 18 ] reported the differences in energy balance and endocrines in mammals and poultry, they also pointed out that animal appetite regulation was mainly through the central nervous system. Recent researchers further indicated that endocrines such as leptin (LEP), reproductive-related hormone, insulin, and AMP-activated protein kinase (AMPK), which were modulated in accordance with the energy level in the diet, were also positively related to the adipose metabolism [ 19 ].…”
Section: Factors On Appetite Regulationmentioning
confidence: 99%